ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARIAH DENGAN PERBANKAN KONVENSIONAL (Studi Kasus pada PT Bank Syariah Mandiri dan PT Bank Mandiri (Persero) Periode 2012 – 2016) - Immanuel Kris Setyabudi, Setyaningsih Sri Utami & Edi Wibowo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this research is to analyze financial performance in terms of theratio of CAR, NPL, ROA, LDR, BOPO and NIM in PT Bank Syariah Mandiri Period.2012 - 2016. Analyze financial performance in terms of the ratio of CAR, NPL, ROA,LDR, BOPO and NIM on PT Bank Mandiri (Persero) 2012 - 2016 Period. Analyzing thedifference of financial performance is reviewed on a CAR, NPL ratio, ROA, LDR, BOPOand NIM on PT Bank Syariah Mandiri and PT Bank Mandiri (Persero) 2012 - 2016Period. Research methods using a case study on PT Bank Syariah Mandiri and PT BankMandiri (Persero), the type of data the data used was qualitative and quantitative data,the source data used the data of skunder. Data analysis technique used is a financialratio analysis and test independent sample t-test. The research results obtainedconclusions that: financial performance of PT Bank Syariah Mandiri in the period 2012- 2016 seen from the CAR, NPL ratio and healthy category entry BOPO, whereas theratio ROA entered the category of less healthy and the LDR entry category is nothealthy. The financial performance of PT Bank Mandiri (Persero) in the period of 2012 -2016 seen from the CAR, NPL ratio, ROA, LDR, BOPO and NIM entry of healthycategory. Financial performance comparison test results that PT Bank Mandiri(Persero) and PT Bank Syariah Mandiri as seen from the CAR, NPL, ROA, LDR, BOPOand NIM, there is a significant differenceKeywords: CAR, NPL, ROA, LDR, BOPO, NIM